Revolutionizing Industrial Manufacturing with Robotic Process Automation (RPA) - Sakshi Tyagi (International Journal of Robotics and Automation in Mechanics, 2023)
Modern nation's primary engine of growth in their economy, industrial production has continuously been looking for creative ways to increase productivity, cut costs, and raise the quality of its output. This industry is undergoing a transformation because to robotic process automation (RPA), which presents a promising solutions to these enduring problems. This study examines how RPA has an enormous effect on industrial manufacturing, examining how it streamlines operations, promotes resource use, and raises the standards of output. We look at how RPA is changing the face of industrial manufacturing through real-world case studies and an in-depth review of its alternatives.
Keywords: Automation; JIT; Robotic Process Automation; artificial intelligence; industrial manufacturing